IBM UPAYA PENINGKATAN DERAJAT KESEHATAN MASYARAKAT YANG OPTIMAL MELALUI SCREENING PENYAKIT TIDAK MENULAR - Ainnur Rahmanti; Anisa Mutiara Hanani; Dana Faricha; Lulu’ah Feby Purwanti; Ni Kadek Krisna Dwi Patrisia; Panji Satria Wiguna (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2022)
Public knowledge to choose adequate and balanced food for individuals and families is still lacking. This is strongly influenced by the level of education, socio-economic and culture. There has been an increase in non-communicable diseases that require serious attention by all parties, both policy makers and the community. Controlling NCDs can be done by modifying risk factors with behavioral changes known as the CERDIK acronym. CERDIK activities: Check your health condition routinely and regularly, Get rid of cigarette smoke and other air pollution, Diligent physical activity with sports and art movements, A healthy diet with balanced calories (low in sugar, salt and fat and rich in fiber) Adequate rest and prioritize safety, Control stress and violence. must be carried out regularly and continuously. The increase in NCDs can be suppressed through controlling risk factors, namely reducing consumption of cigarettes, alcohol, sugar and salt, increasing consumption of fruits and vegetables, increasing physical activity through exercise, preventing obesity, controlling stress with recreational activities and checking blood pressure, blood sugar levels regularly. NCD prevention efforts can be carried out by the community independently through Posbindu activities.